Effect of single and multi-strain probiotics on egg production and blood parameters of local Tegal ducks under village system - Suswoyo, Imam; Ismoyowati, Ismoyowati; Tugiyanti, Elly; Hidayat, Nu’man (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This research aimed to study the effect of single and multi-strain probiotics on egg mass and blood status of local laying ducks under the village system. The method used was an experiment with a Completely Randomized Design. The treatment was single-strain probiotics and multi-strain probiotics with each level of 0/control, 3, 5, and 7 ml/kg feed. Each treatment was replicated 3 times, as a result, there were 21 flocks of duck. Each flock had 40 laying ducks, so there were 840 ducks involved. The treatment was applied for three months. The parameters observed were (1) egg mass; and (2) blood parameters. Results of this study indicated that egg mass was significantly higher (P<0.05) in the treatment group than that in the control group, and not significantly different (P>0.05) between the treatments. Erythrocyte, leucocyte, hemoglobin, and PCV count were not significantly different (P>0.05) between control and treatment, also among treatment groups. It can be concluded that the supplementation of probiotics either single or multi-strain has increased local Tegal duck egg production, however, this supplementation has no effect on blood parameters.